Impairment of mitochondrial calcium buffering links mutations in C9orf72 and TARDBP in iPS-derived motor neurons from patients with ALS/FTD - Dafinca, R; Barbagallo, P; Farrimond, L; Candalija, A; Scaber, J; Ababneh, N; Sathyaprakash, C; Vowles, J; Cowley, S; Talbot, K (Elsevier, 2020)
TDP-43 dysfunction is common to 97% of amyotrophic lateral sclerosis (ALS) cases, including those with mutations in C9orf72. To investigate how C9ORF72 mutations drive cellular pathology in ALS and to identify convergent mechanisms between C9ORF72 and TARDBP mutations, we analyzed motor neurons (MNs) derived from induced pluripotent stem cells (iPSCs) from patients with ALS. C9ORF72 iPSC-MNs have higher Ca2+ release after depolarization, delayed recovery to baseline after glutamate stimulation, and lower levels of calbindin compared with CRISPR/Cas9 genome-edited controls. TARDBP iPS-derived MNs show high glutamate-induced Ca2+ release. We identify here, by RNA sequencing, that both C9ORF72 and TARDBP iPSC-MNs have upregulation of Ca2+-permeable AMPA and NMDA subunits and impairment of mitochondrial Ca2+ buffering due to an imbalance of MICU1 and MICU2 on the mitochondrial Ca2+ uniporter, indicating that impaired mitochondrial Ca2+ uptake contributes to glutamate excitotoxicity and is a shared feature of MNs with C9ORF72 or TARDBP mutations.